Unravelling the Genetic Basis of ACTH-Mediated Aldosterone Hypersecretion in Hypertensive Patients Without Primary Aldosteronism - Mourtzi, Niki (J Endocr Soc, 2021)
Introduction: Primary aldosteronism (PA), a condition characterized by autonomous aldosterone hypersecretion, constitutes the most common cause of secondary hypertension. PA includes both sporadic and familial forms, inherited in an autosomal dominant manner. Recent evidence suggests a higher prevalence of aldosterone excess among hypertensive patients than previously thought, while chronic stress-related ACTH-mediated aldosterone hypersecretion has also been implicated in the pathogenesis of essential hypertension. Objective: To determine whether genetic variations of aldosterone regulating genes could be implicated in the ACTH-mediated aldosterone hypersecretion in hypertensive patients without PA. Methods: Twenty-one hypertensive patients without PA, who exhibited ACTH-mediated aldosterone hypersecretion, underwent Whole Exome Sequencing (WES) on Novaseq 6000 platform (Illumina). As hyper-responders were defined patients whose aldosterone (ALD) and aldosterone-to-renin ratio (ARR) response to ultra-low ACTH stimulation test was above the 97.5(th) percentile values of controls. The cutoff levels for ALD and ARR were 1300 pmol/L and 77 pmol/mIU, respectively. Variant calling was performed according to GATK best practices and VCF files were filtered for variants in 25 genes associated with PA. To identify new susceptibility genes for PA, VCF files were also intersected for variants in ion channels encoding genes involved in pathways responsible for PA. The analysis was restricted to rare variants with gnomAD frequency < 1%. Qualifying variants and pathogenicity were established by employing in silico tools. Copy Number Variant analysis was performed using ExomeDepth algorithm. Results: Eight out of twenty-one patients were heterozygous for rare variants in genes associated with PA, while two patients carried potentially damaging variants in genes encoding ion channels. Specifically, one patient was heterozygous for p.V259M in KCNK5 and one patient was heterozygous for the novel variant p.V221M in KCNK9. Two additional patients carried a predicted pathogenic variant p.R492W in SLC26A2, a gene that has been associated with PA through GWAS. Germline variants in calcium channel genes were also detected in three patients: p.V249I in CACNA1H, p.R462Q in CACNA1D and p.L1801M in CACNA1I, while one patient carried an ultra-rare variant (p.R26L) in ATP13A3. Finally, in two patients we identified rare, likely pathogenic variants in two new susceptibility genes for PA: KCNK16 (p.P255H) and CACNA2D3 (p.V55I). Conclusion: These findings support the notion that mutations in aldosterone synthesis/secretion regulating genes may sensitize zone glomerulosa cells to ACTH stimulation, leading to aldosterone hypersecretion under conditions of stress. We also report two novel candidate susceptibility genes for PA, KCNK16 and CACNA2D3, and one novel variant in KCNK9.